2017
DOI: 10.1002/asna.201613274
|View full text |Cite
|
Sign up to set email alerts
|

Another look at the size of the low‐surface‐brightness galaxy VCC 1661 in the Virgo Cluster

Abstract: The morphologies of individual cluster galaxies are an important path to studying galaxy formation and evolution. Here, we present new wide-field images of the low-surface-brightness Virgo Cluster dwarf galaxy VCC 1661. The extant literature lists a broad range of radii for this object, covering a factor of more than four, depending on the filters used and the details of the analyses. While some studies find a radius typical of other Virgo dwarfs and note the normality of this object, any larger spatial extent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Findings of dwarf galaxies with extreme LSB have been reported two decades ago (e.g., Impey et al 1988;Bothun et al 1991). UDGs were detected in the Coma cluster using deep low-resolution imaging data obtained with small telescopes (van Dokkum et al 2015a), and more UDGs were found in nearby galaxy clusters since then (Koda et al 2015;Mihos et al 2015;Muñoz et al 2015;van der Burg et al 2016;Koch et al 2017;Román & Trujillo 2017a). Differing from the classical LSB galaxies that usually have a central surface brightness down to µ(B, 0) ∼ 22 − 23 mag arcsec −2 (Impey & Bothun 1997;Impey et al 2001;Ceccarelli et al 2012;Geller et al 2012), UDGs have a much lower central surface brightness (µ(g, 0) = 24 − 26 mag arcsec −2 ), but their half-light radius r e > 1.5 kpc is comparable to that of typical L * galaxies, and their stellar mass (<∼ 10 8 M ⊙ ) is two orders of magnitude lower (van Dokkum et al 2015a).…”
Section: Introductionmentioning
confidence: 92%
“…Findings of dwarf galaxies with extreme LSB have been reported two decades ago (e.g., Impey et al 1988;Bothun et al 1991). UDGs were detected in the Coma cluster using deep low-resolution imaging data obtained with small telescopes (van Dokkum et al 2015a), and more UDGs were found in nearby galaxy clusters since then (Koda et al 2015;Mihos et al 2015;Muñoz et al 2015;van der Burg et al 2016;Koch et al 2017;Román & Trujillo 2017a). Differing from the classical LSB galaxies that usually have a central surface brightness down to µ(B, 0) ∼ 22 − 23 mag arcsec −2 (Impey & Bothun 1997;Impey et al 2001;Ceccarelli et al 2012;Geller et al 2012), UDGs have a much lower central surface brightness (µ(g, 0) = 24 − 26 mag arcsec −2 ), but their half-light radius r e > 1.5 kpc is comparable to that of typical L * galaxies, and their stellar mass (<∼ 10 8 M ⊙ ) is two orders of magnitude lower (van Dokkum et al 2015a).…”
Section: Introductionmentioning
confidence: 92%
“…Apart from some exceptions, there is a visible trend that as galaxies become redder they also become smaller. VCC1661 is the galaxy with the largest effective radius (for a detailed study of this extended galaxy see Koch et al 2017).…”
Section: Reasons For the Scatter In Cmrmentioning
confidence: 99%
“…The images used in this work were taken as part of the HERON survey, and details of their reduction are given in Rich et al (2019) alongside a general characterization of the galaxies, for instance in terms of their halo sizes. Imaging for the two targets was acquired in October and November 2011 with the 28-inch Centurion (C28) telescope at the Polaris Observatory Association in Lockwood Valley, California (Rich et al 2012(Rich et al , 2019Brosch et al 2015;Koch et al 2017). The pixel scale of the detector is 0.82 pixel −1 , which for NGC 720 has been resampled by a factor of two in either dimension.…”
Section: Observations: Centurion 28 Imagingmentioning
confidence: 99%
“…However, at its absolute magnitude, this merging candidate appears too large by a factor of a few, when compared to typical galaxies of similar magnitude. Its corresponding half-light radius is 2.4 ± 0.3 kpc, and an investigation of systematically more extended objects is often used to confirm the presence and absence of tidal disruptions (Koch et al 2017). Indeed, the contender within NGC 2768 lies within ±1.5 mag of the strongly disrupted NGC 4449B (Rich et al 2012) and HCC-087 (Koch et al 2012) at similarly large radii.…”
Section: Pelops In Contextmentioning
confidence: 99%